Consumption of a multi-deficient diet causes dynamic changes in the intestinal morphofunctional barrier, body composition and impaired physical development in post-weaning mice. Issue 5 (14th March 2023) - Ribeiro, Samilly Albuquerque; Rodrigues, Francisco Adelvane de Paula; Clementino, Marco Antonio de Freitas; Veras, Herlice do Nascimento; Siqueira, Rômmulo Celly Lima; de Medeiros, Pedro Henrique Quintela Soares; Pereira, Jeanine Morais; Guanabara Júnior, Márcio Flávio Araújo; de Sousa, José Kleybson; Santos, Ana Karolina Silva; dos Santos, Armênio Aguiar; Maciel, Bruna Leal Lima; et al.
Abstract: Few studies have focused on nutrient-deficient diets and associated pathobiological dynamics of body composition and intestinal barrier function. This study evaluated the impact of a nutrient-deficient diet on physical development and intestinal morphofunctional barrier in mice. C57BL/6 (21 days of age) mice were fed a Northeastern Brazil regional basic diet (RBD) or a control diet for 21 d. The animals were subjected to bioimpedance analysis, lactulose test, morphometric analysis and quantitative reverse transcription-PCR to evaluate tight junctions and intestinal transporters. RBD feeding significantly reduced weight ( P < 0·05) from day 5, weight gain from day 3 and tail length from day 14. The intake of RBD reduced total body water, extracellular fluid, fat mass and fat-free mass from day 7 ( P < 0·05). RBD induced changes in the jejunum, with an increase in the villus:crypt ratio on day 7, followed by reduction on days 14 and 21 ( P < 0·05). Lactulose:mannitol ratio increased on day 14 ( P < 0·05). Changes in intestinal barrier function on day 14 were associated with reductions in claudin-1 and occludin, and on day 21, there was a reduction in the levels of claudin-2 and occludin. SGLT-1 levels decreased on day 21. RBD compromises body composition and physical development with dynamic changes in intestinal barrier morphofunctional. RBD is associated with damage to intestinal permeability, reduced levels of claudin-1 and occludin transcripts and return of bowel function in a chronic period.